Grazing induces direct and indirect shrub effects on soil nematode communities. (June 2018) - Wang, Xiangtai; Nielsen, Uffe N.; Yang, Xiaoli; Zhang, Limin; Zhou, Xianhui; Du, Guozhen; Li, Guixin; Chen, Shuyan; Xiao, Sa
Abstract: It is well established that aboveground-belowground interactions moderate ecosystem functioning. The direct and indirect effects of plants on belowground communities have been explored by many studies; however, few studies have considered how grazing moderate the direction and intensity of these effects. In this study, we explored how grazing by yak moderates the effect of the shrub Dasiphora fruticosa on nematode communities through a short-term shrub removal experiment in a grazed and ungrazed alpine meadow on the Tibetan plateau. We used structural equation modelling (SEM) to assess both the direct effects of D. fruticosa and indirect effects mediated by changes in understorey vegetation composition and edaphic properties, on nematode communities. The presence of D. fruticosa had no significant impact on the abundance of nematodes in the ungrazed meadow. By contrast, D. fruticosa had a strong negative direct effect on nematode abundance, but also a positive indirect effect due to greater grass biomass, in the grazed meadow. The effect of D. fruticosa on nematode community composition was limited, with only a marginally significant direct effect on nematode community composition in the grazed meadow. Instead, nematode community composition was strongly related to soil water content and organic matter content in both grazing treatments, and soil pH in the grazed meadow. Our results indicate that grazing moderate aboveground-belowground linkages through direct and indirect shrub effects on nematode abundance, but have limited effects on nematode community composition. Highlights: Grazing modifies shrub effects on soil nematode communities. Shrub had no significant impact on the nematode abundance in the ungrazed meadow. Instead, shrub had strong effect on the nematode abundance in the grazed meadow. Nematode community composition weakly related to shrub induced changes.